The Novaya Zemlya Event of 31 December 1992 and Seismic Identification Issues: Annual Seismic Research Symposium (15th) Held in Vail, Colorado on 8-10 September 1993 - ADVANCED RESEARCH PROJECTS AGENCY ARLINGTON VA (1993)
On December 31, 1992 a small (mb 2.5) event (hereafter 921231) was detected on Novaya Zemlya by the Threshold Monitor (TM) system. The TM system uses data from the on-line array network to continuously monitor seismic amplitude levels for a number of specified experimental target sites, including the Russian nuclear test range on Novaya Zemlya. The method involves continuous beamforming (i.e., time-aligning and summing the traces for each regional array) for the target beam-steering points, to extract parameters of the beams for continuous assessment of the upper magnitude limit of events at the target site that would go undetected by the Scandinavian array network. When events occur that are above the network noise level, they appear as peaks on the TM beams and are thus tagged for detailed off-line analysis. The 921231 event was detected in this way and was identified as an event that might be of particular interest to ARPA. On receipt of the information ARPA decided to use the 921231 event as an example to test the effectiveness of seismic identification tools and systems that are being developed within the nuclear monitoring research community. The reason for focusing on this particular event is that it had a number of characteristics that might be typical of events that would be of concern in a future CTBT or NPT monitoring environment Original contains color plates: All DTIC reproductions will be in black and white.